The combined impact of chronic kidney disease and ulcer severity on incident cardiovascular events in patients with diabetes‐related foot ulceration - Nick S. R. Lan; Jonathan Hiew; Ivana Ferreira; J. Carsten Ritter; Laurens Manning; P. Gerry Fegan; Emma J. Hamilton; Girish Dwivedi (Physiological Reports)
Abstract In patients with diabetes‐related foot ulceration (DFU), ulcer severity and chronic kidney disease (CKD) portend worse outcomes. We evaluated the combined impact of a severe ulcer with CKD on major adverse cardiovascular events (MACE) in patients with DFU. Ulcer severity was defined using the SINBAD (site, ischaemia, neuropathy, bacterial infection, area, depth) classification, dividing into low (1–3) or high (4–6). CKD was defined as an estimated glomerular filtration rate <60 mL/min/1.73 m2. Patients were categorized into four groups based on SINBAD and CKD category. MACE was defined as hospitalization for myocardial infarction, stroke or transient ischemic attack, or heart failure. Of 497 patients, 236 (47.5%) were SINBAD‐low/CKD‐absent, 80 (16.1%) SINBAD‐high/CKD‐absent, 127 (25.6%) SINBAD‐low/CKD‐present, and 54 (10.9%) SINBAD‐high/CKD‐present. The median follow‐up was 410 (interquartile range 242–576) days for MACE and 387 (221–549) days for MACE or all‐cause mortality. SINBAD‐high/CKD‐present was associated with significantly higher MACE (SINBAD‐low/CKD‐absent 4.2%; SINBAD‐high/CKD‐absent 7.5%; SINBAD‐low/CKD‐present 9.5%; SINBAD‐high/CKD‐present 33.3%; log‐rank p < 0.001) and MACE or all‐cause mortality (SINBAD‐low/CKD‐absent 5.5%; SINBAD‐high/CKD‐absent 13.8%; SINBAD‐low/CKD‐present 17.4%; SINBAD‐high/CKD‐present 53.7%; log‐rank p < 0.001). SINBAD‐high/CKD‐present was associated with MACE (p < 0.001) and MACE or all‐cause mortality (p < 0.001) after multivariate adjustment. Severe DFU with CKD amplifies the risk of MACE in patients with DFU, suggesting important implications for cardiovascular risk assessment.